Unveiling the antimicrobial and antibiofilm potential of biosurfactant produced by newly isolated Lactiplantibacillus plantarum strain 1625 - Thakur, Babita; Kaur, Sukhminderjit; Dwibedi, Vagish; Albadrani, Ghadeer M.; Al-Ghadi, Muath Q.; Abdel-Daim, Mohamed M. (Frontiers in Microbiology, 2024)
The present study aimed to characterize the biosurfactants synthesized by lactic acid bacteria (LAB) obtained from fermented foods, optimize the conditions for increasing the yield of biosurfactants and explore their antimicrobial and antibiofilm potential. Out of the 26 LAB isolates, isolate BS2 showed the highest biosurfactant production as indicated in the oil displacement test, drop collapse and emulsification activity. BS2 was identified as Lactiplantibacillus plantarum 1625 using 16s-rRNA gene sequencing and phylogenetic analysis. The biosurfactant produced by BS2 was identified as an anionic glycol-lipo-proteins by employing Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The biosurfactants produced by L. plantarum 1625 demonstrated strong antibacterial and antibiofilm characteristics against pathogenic strains such as Staphylococcus aureus MTCC 1049, Escherichia coli MTCC 1587, and Pseudomonas putida MTCC 1655. The minimal inhibition concentration value of antibacterial activity was found to be 0.1mg/mL with the inhibition percentage ranging from 90-95%. Further, the effect of temperature, pH, and substrate composition on biosurfactant production was also studied to enhance it production using the Box-Behnken Design approach of Response surface methodology (RSM). Application of biosurfactant led to a considerable decrease in biofilm-forming harmful bacteria, as proven by scanning electron microscopy analysis. The results highlight the potential uses of biosurfactants in distinct industries, and biotechnological contexts, especially in the creation of new antimicrobial and antibiofilm agents.